Synonymic relationship in tourism terminology - Miyassarov , Eldor (The Lingua Spectrum, 2025)
This article comprehensively analyzes the synonymous relationships of terms used in the tourism sector. Identifying the synonymous characteristics of commonly encountered tourism terms is crucial as it helps to reveal the differences in their practical application. During the study, scientific articles related to tourism, specialized dictionaries, and expert opinions were utilized to identify synonymous units, and their semantic, contextual, and pragmatic features were thoroughly examined. Terms commonly used in the tourism field were analyzed as examples, and the differences in their usage were presented in detail. Using the comparative method, key terms in Uzbek and French were analyzed, and detailed information about their linguistic and cultural characteristics was provided. The cultural connotations and regional variations of tourism terms were also studied, shedding light on how these factors influence their practical application. The results indicate that the systematic standardization and adaptation of tourism terminology are essential not only for improving effective communication in the tourism sector but also for enhancing knowledge exchange in the international tourism market. Moreover, the use of clear and understandable terminology plays a significant role in improving service quality in the tourism industry and offering solutions that meet customer needs.